Phase content, tetragonality, and crystallite size of nanoscaled barium titanate synthesized by the catecholate process: Effect of calcination temperature - Maison W. (2014)
A modified catecholate process has been applied to synthesize high purity barium titanate powders in the submicron range. A barium titanium-catechol complex, Ba[Ti(C6H4O2)3] was prepared from TiCl4, C6H4(OH)2 and BaCO3, freeze-dried, and calcined for 3 h at temperatures between 600 and 1300 °C. Phase transformation and crystallite size of the calcined powders were investigated as a function of the calcination temperature by X-ray diffraction methods, and particle morphology and size were studied by scanning electron microscopy. With increasing calcination temperature, BaTiO3 transformed from the (pseudo)cubic to the ferroelectric tetragonal phase. The tetragonality (c/a-1) increases with increasing calcination temperature and increasing crystallite size, respectively. Higher temperatures clearly favoured particle growth and the formation of large and hard agglomerates. The crystallite size of the tetragonal phase increased from <60 nm at 600-800 °C to 1237 ± 344 nm at 1300 °C. © 2002 Elsevier Science Ltd. All rights reserved.